CFD Simulation of Scram Jet Inlet - Teja, Letu; Dasu, P. (Journal of Neonatal Surgery, 2025)
In order to provide the definition of a scramjet engine, the definition of a ramjet engine is first necessary, as a scramjet engine is a direct descendant of a ramjet engine. Ramjet engines have no moving parts, instead operating on compression to slow free stream supersonic air to subsonic speeds, thereby increasing temperature and pressure, and then combusting the compressed air with fuel. Lastly, a nozzle accelerates the exhaust to supersonic speeds, resulting in thrust. Due to the deceleration of the free stream air, the pressure, temperature and density of the flow entering the burner are “considerably higher than in the free stream”. At flight Mach numbers of around Mach 6, these increases make it inefficient to continue to slow the flow to subsonic speeds. In this thesis, generally a Scramjet Engine starts at a hypersonic frees Stream Mach no. 5.00. In order to propel to those speeds, we use turbojet engines which propel to around 3.00-4.00 Mach and from there the ramjet picks upon and starts to propel to start the scramjet engine. If we increasing the scramjet engine starting Mach number to say 3.0, 5.0, 7.0 and 9.0. We can eliminate one propulsion engine, i.e., ramjet engine and thus reducing weight and complexity. The design for such a scramjet engine is carried out in this project considering only the inlet designs and the flow analysis is carried out in CFD. FLUENT is used to cover the flow analysis.